Islam and the State in Indonesia: Munawir Sjadzali and Development of a New Theological Underpinning of Political Islam - Effendy, Bahtiar (Studia Islamika, 1995)
The relationship between Islam and the state is one of the complex issues in Indonesia. Since the beginning of independence, the debate on Islam and the country has a lot of coloring the history of this nation. Most Indonesian Muslims are eager remedy make Islam the state religion and ideology. This desire has repeatedly attempted, but always failed. Both non-Muslims and most Muslims do not want Islam serve as the official state religion and ideology underlying system state. History proves that both parties have always managed to ward off the desire first.Even so, it does not mean the struggle among Muslims who want Islam as a state ideology has been stopped by the failure. Efforts in that direction continue to be run by the figures from the beginning wanted a formalization of Islam in the state system. At the beginning of the New Order, some of the fight for the restoration of Islamic parties that dissolved during the reign of Indonesia's first president Sukarno. They also want the implementation of the Jakarta Charter which clearly guarantees the existence of Islam in the country.DOI:Â 10.15408/sdi.v2i2.836